(untitled) (Social Science Review, 2025)
While countries across the world were crippled by COVID-19 during 2020-2021, there had been substantial variations in death and infection rates. Some countries found themselves overwhelmed, while others remained relatively spared. The reasons behind such discrepancies remain largely unclear. This study aims to elucidate the determinants of death and infection rates associated with COVID-19 across various countries, utilizing multivariate regression analysis and the least absolute shrinkage and selection operator (LASSO) regression. The OLS estimates show that the ageing population and hospital beds per capita are significantly associated with the fatality rate of COVID-19, while urbanization has a positive correlation with the infection rate. The study suggests that enhancing the capacity of healthcare systems can play a crucial role in substantially reducing fatality rates associated with COVID-19. Social Science Review, Vol. 42(1), June 2025, pp. 1-20